Elite capture, civil society and democratic backsliding in Bangladesh, Thailand and the Philippines. Issue 1 (2nd January 2021) - Lorch, Jasmin
ABSTRACT: While the literature on democratic backsliding has not yet systematically investigated how civil society influences backsliding processes, it generally assumes that civil society organizations (CSOs) act as a counter to democratic backsliding. This article contests this assumption by showing that, despite all three countries having vibrant civil societies, CSOs have so far failed to counter democratic backsliding in Bangladesh, Thailand and the Philippines. It argues that in weakly institutionalized democracies, CSOs are easily captured by political elites, a condition that brings their undemocratic potential to the fore.